A social constructs model for student satisfaction in architectural design studios within blended learning environments at Malaysia's Public Higher Education Institution / Sayed Muhammad Aiman Sayed Abul Khair - Sayed Abu Khair, Sayed Muhammad Aiman (2025)
The research explores how social constructs shape students' satisfaction in the blended learning environments (BLE) of architectural design studios (ADS) at the Malaysian public higher education institutions (HEIs) context. The COVID-19 pandemic caused a sudden shift towards online and blended learning, disrupting the traditional model of the studio on which architectural education is grounded. The social, collaborative, and interactive dynamics integral to studio-based learning (SBL) were being significantly challenged, raising concerns about maintaining student satisfaction and engagement in a blended educational framework. Notably, this shift also revealed opportunities for pedagogic innovation, especially in integrating digital tools and blended methodologies. The research identifies a critical gap in how the social constructs of Social Interaction, Social Support, Social Presence, Social Influence, Social Identity, and Social Space influence students' satisfaction in BLE for ADS.